2016
DOI: 10.1111/plb.12466
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of several seed viability markers in individual recalcitrant seeds of Eugenia stipitata McVaugh with totipotent germination

Abstract: The use of biochemical seed viability markers is often compromised by the unknown partitioning of analytes in bulk seed lots consisting of inseparable populations of viable and nonviable seeds. We took advantage of an unusual morphological syndrome found in the recalcitrant, undifferentiated seeds of Eugenia stipitata: one seed can be cut into several parts, each of which can germinate and develop into seedlings. We used four seed parts from one individual seed to analyse seed moisture content (MC), seed viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
0
17
0
4
Order By: Relevance
“…Another important characteristic is that, in addition to the single embryonic axis, which is microscopic (Justo et al, 2007), Journal of Seed Science, v.40, n.3, p.221-236, 2018 these seeds are able of producing new roots and even entire seedlings from cotyledon cells (Anjos and Ferraz, 1999;Calvi et al, 2016), a characteristic rarely found in other species (Malik et al, 2005;Joshi et al, 2006;Asomaning et al, 2011). However, it is rare the formation of more than one root or seedling from a single seed at the same time.…”
Section: Strategies To Ensure the Perpetuation Of The Species With Rementioning
confidence: 99%
“…Another important characteristic is that, in addition to the single embryonic axis, which is microscopic (Justo et al, 2007), Journal of Seed Science, v.40, n.3, p.221-236, 2018 these seeds are able of producing new roots and even entire seedlings from cotyledon cells (Anjos and Ferraz, 1999;Calvi et al, 2016), a characteristic rarely found in other species (Malik et al, 2005;Joshi et al, 2006;Asomaning et al, 2011). However, it is rare the formation of more than one root or seedling from a single seed at the same time.…”
Section: Strategies To Ensure the Perpetuation Of The Species With Rementioning
confidence: 99%
“…The seeds from both lots were submitted to a pre-germination treatment, where the fibrous seed coat was removed from the radicle protrusion region and at the opposite end of the seed (Calvi et al, 2017).…”
Section: Germination Testsmentioning
confidence: 99%
“…Glutathione analysis, viability staining and determination of seed moisture content After flooding, seeds of Lot 2 were decoated, and seed quarters were used for viability staining, seed MC determination, and analysis of GSH and GSSG in each individual seed (Calvi et al, 2017). Two quarters were immediately frozen in liquid nitrogen and freezedried for 3 days to prevent redox reactions prior to analysis.…”
Section: Germination Testsmentioning
confidence: 99%
“…Studies performed with cuttings of Eugenia spp. seeds showed that more than one plant can be obtained from one seed (Silva et al, 2005;Amador and Barbedo, 2011;Teixeira and Barbedo, 2012;Prataviera et al, 2015;Calvi et al, 2016). It was also found that dependence on cuttings for development of these tissues indicates that injuries in seeds may initiate some process of inducing formation of new roots and seedlings, or they may block the autoinhibition of these formations in seeds (Delgado and Barbedo, 2011;Amador and Barbedo, 2015).…”
Section: Introductionmentioning
confidence: 99%